MODEL PENGEMBANGAN SUMBER DAYA NELAYAN BERWAWASAN AGRIBISNIS DI KOTA BENGKULU - Sriyoto, Sriyoto; Sumantri, Bambang (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
Globalization era characterized by increasingly open and integrated commodity markets both between countries and between regions including fishery commodities. This imply that an increasing of product quality through empowering fishing resource is a significant step to be able to enter an era of competition. This study aims to identify the performance of the fisherman resources, a partnership between fishermen and fish entrepreneurs, and formulate alternative development model of fisherman resource with agribusiness minded. The research method is based on the survey method (primary and secondary data). Descriptive methods, descriptive statistics, and methods of the Logical Framework Analysis (LFA) are used to analyse data. The results showed that the fishermen, in general, are in the productive age with the typology of the nuclear family; more than half of the fishermen have junior secondary education level; fishing experience is categorized long enough that 18.26 years; fishermen have the motivation to keep working as a fisherman and a hierarchy of compassion (safety needs) by 60%; technical and managerial skills possessed by fishermen in general is quite good but the managerial aspects of fishing is still not good. Furthermore, most fishermen have high accessibility to the means of fishing, but only a few fishermen who use capital loans of non-formal institutions, mostly fishermen actively looking for information about fishing technology, relationship between the fishermen and fish processors/collectors is a patron client pattern, the market formed in the study area is oligopsonistic market, and net income of fishermen can be categorized enough. There are two alternative models of fisherman resources development with agribusiness minded: training model with a training for impact approach, and education model.